The Irregular Terrain of Human Subjects Research Regulations - Forster, David (The Hastings Center report, 2014)
The overlap and differences between the parallel regulatory systems for research create ample room for confusion and missteps, as discussed by Barbara Bierer and Mark Barnes in their report in this supplement. In practice, beyond the inherent differences in the two systems of regulations themselves, there are many issues that further complicate the application of these regulations. These include the variation in size of the institutions receiving PHS funding, the increased prevalence of multisite research, the allocation of research conduct and oversight to external organizations, and the variability in assignment of human subject protection roles between the IRB and the institution.